PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG GO PUBLIK DI BURSA EFEK INDONESIA - Retno Widuri (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2009)
The study titled "Impact On Financial Ratios Share Price Manufacturing Company of Go Public In Indonesia Stock Exchange". Aiming to know and analyze the influence of leverage ratios, liquidity ratios, profitability ratios of stock prices in manufacturing companies listed on the Stock Exchange. Population in this research are all manufacturing companies listed on the Stock Exchange since 2004 until 2006, where the sample is taken by the method of purposive sampling. 154 companies selected from 57 companies that made the research sample. This research method Partial Least Square Regression (PLS regression).The results of this study indicate that 1) the leverage ratio on a proxy with Debt to Equity Ratio (DER) and a significant negative impact on stock prices, 2) liquidity ratio on a proxy with Quick Ratio (QR) do not have real impact on stock prices, 3) ratio of activity which on a proxy with Inventory Activity (IA) and a significant positive impact on stock prices and Sales to Current Assets (SCA) does not have real impact on stock prices, 4) profitability ratio which on a proxy with Return On Equity (ROE) and a significant positive impact on stock prices.The results imply that 1) investors should consider leverage (represented by the Debt to Equity Ratio (DER), the ratio of activity especially Inventory Activity (IA), and profitability ratios in the form of Return On Equity (ROE) in predicting stock prices that will be used to invest , 2) For further research is recommended to use the proxy financial ratios more complete